Adoption of Extended Theory of Planned Behavior to Halal Food Purchasing Decision Admist Pandemic - Fuad Hasyim (Journal of Islamic Economic Laws, 2022)
This study aims to see whether there has been a change in the pattern of consumption of halal food during a pandemic. This study used a sample of the Soloraya Residence with a random sampling distribution technique using an online questionnaire (G-form). The quantitative research method is carried out using the Extended TPB approach, and processed with the Structural Equation Modeling Technique. The results show that all constructs namely attitude, subjective norms, perceived behavioral control, religiosity and descriptive norms affect the purchase intention of halal food and the decision to buy halal food. By using a pandemic condition as a dummy variable, the results obtained are differences in decision making to buy halal food before and during a pandemic. This means that there is a pattern of changes in people's consumption that tends to choose halal food, even though the changes are small.